The investigation of frame disturbance (fd) in perceptual evaluation speech quality (PESQ) as a perceptual metric - Jusoh, Ahmad Zamani; Togneri, Roberto; Nordholm, Sven; Sulaiman, Nadzril; Khairolanuar, Muhamad Haziq (Medwell Journals, 2015)
Satisfying customers’ needs economically is one of the important aspects in mobile communication industry. Provider should cater a good and consistent quality of service as expected by the customers. Hence, it is amounts to controlling the speech quality perceived by the customers. However, to control the speech quality, the reliable measurement of the speech quality must be determined first, then exercising direct control of it. Traditionally, the quality of speech at the end user has been monitored and controlled based on radio link measurements such as the Signal Interference Ratio (SIR), Bit Error Rate (BER), or Frame Error Rate (FER). The truly perceive speech quality is measure through subjective listening tests. However, this method is not practical for real-time day to day applications. Newly,objective quality measurement algorithms have been developed to replace the subjective quality measurement with considerable accuracy. P.862 Perceptual Evaluation of Speech Quality (PESQ) model is the state of art on the referenced objective measurement method in the International Telecommunication Union’s Telecommunication Standardization Sector (ITU-T). PESQ is calculated based on the so-called Frame Disturbance (FD). In this paper FD is investigated as a perceptual metric for control of speech quality in modern communication systems replacing the conventional metrics.